Lectin-based electrophoretic analysis of the expression of the 35 kDa inter-alpha-trypsin inhibitor heavy chain H4 fragment in sera of patients with five different malignancies - Mohamed, E.; Abdul-Rahman, P.S.; Doustjaialil, S.R.; Chen, Y.; Lim, B.K.; Omar, S.Z.; Bustam, A.Z.; Singh, V.A.; Mohd-Taib, N.; Yip, C.H.; Hashim, Onn Haji (2008)
A 35 kDa glycoprotein whose abundance was previously demonstrated to be enhanced in sera of patients with endometrial adenocarcinoma (n = 12), was isolated from pooled sera of three of the cancer patients using champedak galactose-binding lectin affinity chromatography in the present study. Subjecting it to 2-DE and MS/MS, the glycoprotein was identified as the O-glycosylated fragment of inter-a-trypsin inhibitor heavy chain H4 (ITIH4). When compared to control sera (n = 17), expression of the 35 kDa ITIH4 cleavage fragment was demonstrated to be significantly enhanced in sera of patients with breast carcinoma (n = 10), epithelial ovarian carcinoma (n = 10), and germ cell ovarian carcinoma (n = 10) but not in patients with nasopharyngeal carcinoma (n = 13) and osteosarcoma (n = 7). The lectin-based electrophoretic bioanalytical method adopted in the present study may be used to assess the physiological relevance of ITIH4 fragmentation and its correlation with different malignancies, their stages and progression.